Crafting a Class : College Admissions and Financial Aid, 1955-1994. - Duffy, Elizabeth A. (Princeton legacy library., 2014)
Admissions and financial aid policies at liberal arts colleges have changed dramatically since 1955. Through the 1950s, most colleges in the United States enrolled fewer than 1000 students, nearly all of whom were white. Few colleges were truly selective in their admissions; they accepted most students who applied. In the 1960s, as the children of the baby boom reached college age and both federal and institutional financial aid programs expanded, many more students began to apply to college. For the first time, liberal arts colleges were faced with an abundance of applicants, which raised.